Effect of Cadmium on Growth, Bacoside A, and Bacopaside I of Bacopa monnieri (L.), a Memory Enhancing Herb - Poonam Gupta; Sayyada Khatoon; P. K. Tandon; Vartika Rai (The Scientific World Journal)
Bacopa monnieri (L.) is an important medicinal plant mainly known as a memory enhancing herb. It is important to see the effect of metal pollution on its active constituents. In this context, efforts have been made to observe the effect of Cd on the triterpenoid saponins bacoside A and bacopaside I in this plant. The influence of the metal on growth parameters like protein, chlorophyll content, and biomass has also been observed. It is interesting to note that the bacoside A and bacopaside I gradually increased by the Cd treatment up to 10 μM and then decreased at higher concentrations, that is, 50 and 100 μM, but the concentration of these components was more in all the treated plants as compared to control. On the contrary, protein, chlorophyll content, and biomass decreased with the increase in metal concentration and exposure duration due to metal toxicity.